Evaluation of drought-tolerance in some tropical wheat genotypes (Triticum aestivum L.) at different osmotic-stress levels - Muhammad Kadir; Kaimuddin Kaimuddin; Yunus Musa; Muh Farid Badaruddin; Amin Nur (Jurnal Ilmu Pertanian, 2020)
Abiotic factors, such as temperature and drought, were the main factors limiting the cultivation under the tropical condition. Two-stage experiments were conducted to examine the drought-tolerant potential of some wheat genotypes against the osmotic stress under the tropical condition at the Laboratory and Greenhouse of Hasanuddin University and Indonesian Cereal Research Institute. The experiments were arranged in a randomized block design with the split-plot pattern and respectively provided with four and three replications. The main plot was potential osmotic stress (0, -0. 33 , and -0.67 MPa) and the sub-plot was selected wheat genotypes (17 genotypes). The results indicated that based on the germination percentage, shoot/root ratio, proline content, stomatal behavior, and relative water content, the wheat lines of O/HP-78-A22-3-7, WBLL*2KURUKU, O/HP-6-A8-2-10, and O/HP-22-A27-1-10 were identified to have better drought-tolerance than the others genotypes based on the analysis of responses to parameters observed. The positively adaptive response of some tropical wheat genotypes to drought stress may be used as a potential donor for further development of drought-tolerant wheat varieties under the tropical climate in Indonesia.